Teaching at the Right Level-based Project-based Learning on Mathematical Connections of Fourth Grade Elementary School Students - Kafah, Anisa; Efianingrum, Ariefa; Kholifah, Lulu; Pangestu, Anggit; Ujang Sugara (International Journal of Elementary Education, 2024)
Learning in primary schools currently follows the direction of the Merdeka Curriculum which prioritises independent learning according to the learners' own abilities. Mathematical connections are still important things that students must have for their daily lives. This study aims to analyse the effect of implementing the TaRL-based PjBL model on mathematical connections, especially in mathematics subjects. This quasi-experimental study used saturated sampling of 18 grade IV students. A pretest-posttest group design was used in one group. The research used tests. In this study, descriptive analysis technique was used for data analysis, which used sequential sample t test. Before hypothesis testing, prerequisite tests such as normality and homogeneity tests were conducted. When compared to students before treatment, the application of TaRL-based PjBL model was proven to improve their mathematical connection. Furthermore, data processing was carried out with tcount ≥ ttable 5.702 > ttable 2.10982) which indicates that H0 is rejected and H1 is accepted, meaning that there is a positive effect of the TaRL-based PjBL model on students' mathematical connections in class IV elementary schools.